Appraisals to affect: Testing the integrative cognitive model of bipolar disorder. (27th March 2015) - Palmier‐Claus, Jasper E.; Dodd, Alyson; Tai, Sara; Emsley, Richard; Mansell, Warren
Abstract : Objective: Cognitive models have suggested that extreme appraisals of affective states and maladaptive affect regulation strategies are important in the development of bipolar symptomatology. Little is known about the pathway by which these appraisals and behaviours interact in the formation of activated and depressed affective states. This study tested the predictions that (1) ascent behaviours mediate the relationship between positive appraisals of activated mood and activation; and (2) descent behaviours mediate the relationship between negative appraisals of activated mood and depression. Method: A total of 52 individuals with a DSM‐IV diagnosis of bipolar I or II disorder (confirmed by structured interview) completed biweekly assessments of affect regulation behaviours and mood for 4 weeks. Positive and negative appraisals of affective states were assessed at baseline through the Hypomanic Attitudes and Positive Prediction Inventory. Multilevel mediation analysis was used to explore the data. Results: Ascent behaviours partially mediated the relationship between positive appraisals of activated mood and activation. Descent behaviours, but not negative appraisals of activated mood, predicted levels of depression indicating the absence of a mediation effect. Conclusion: The results suggest that positive appraisals of activated mood can escalate activation in individuals with bipolar disorder. Such appraisals may be inherently rewarding and reinforcing directly elevating levels of activation, whilst increasing individuals' use of ascent behaviours. The results are consistent with the view that appraisals and behaviours should be targeted during cognitive behavioural therapy for bipolar disorder. Practitioner points: It may be beneficial to target positive appraisals of activated mood in cognitive behavioural therapy for mania. Cognitive behavioural therapists may also wish to focus on identifying and targeting individuals' use of ascent behaviours to reduce highly activated states.